Ravishing maidens : writing rape in medieval French literature and law - Gravdal, Kathryn (New cultural studies series., 1991)
In this study of sexual violence and rape in French medieval literature and law, Kathryn Gravdal examines an array of famous works never before analyzed in connection with sexual violence. Gravdal demonstrates the variety of techniques through which medieval discourse made rape acceptable: sometimes through humor and aestheticization, sometimes through the use of social and political themes, but especially through the romanticism of rape scenes.